PENGARUH BERCERITA TERHADAP PERCAYA DIRI ANAK USIA 5-6 TAHUN DI TK ISLAM SEMESTA PONTIANAK - Rukmana, Hajar; Ali, Muhamad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to defermine differences in childern?s confidence. Before znd after the storytelling method is applied, whether there are differences in childern?s confidence before and after the medhod of storytelling is applied. This type of research is research using experimental methods with one-group pretest- posttest design, datacollection using observation and documentation activities.The sample in this study was children aged 5-6 years in group B  consisting of 6 girls and 8 boys.  Based on the analysis of data that has been done, the results of a study entitled the effect of the method of telling stories on the confidence of chidern aged 5-6 years in the TK Islam Semesta Khatulistiwa Pontianak, there is very big influence it is evidenced by the acquisition of the average child at pretest which is 7,071 and the average value at posttest is 10.  Then from the results the t-test calculation is done an the result the show that t-hitung > t-tabel 7,614> 1,604. Which means that there is a difference in childern?s confidence. After being treated using the storytelling medhod. Then to find out how much influence the medhod of storytelling on a child?sconfidenceistested for effect size and result obtained are 2, 035> 1,00 which means that the medhod of storytelling has a strong influence on the confidence of children aged 5-6 years at TK Islam Semesta Khatulistiwa Pontianak and in the strong categoryKeywords: Children Aged 5-6 Years, Self Confidence, Storytelling Medhod.